TREC and KREC in very preterm infants: reference values and effects of maternal and neonatal factors. (2nd December 2021) - Remaschi, Giulia; Ricci, Silvia; Cortimiglia, Martina; De Vitis, Elisa; Iannuzzi, Laura; Boni, Luca; Azzari, Chiara; Dani, Carlo
Abstract: Objective: T-cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC) assays have been used for severe combined immunodeficiencies newborn screening (NBS). We assessed TREC and KREC NBS values in preterm infants and investigated if perinatal characteristics affect their values. Methods: We performed a retrospective study collecting data from TREC and KREC NBS database and from mothers' and infants' medical charts. Results: TREC and KREC values were lower in preterm infants born at 23–31 or 32–36 weeks of gestation than in term infants. Gestational age <28 weeks of gestation, leukopenia, and hypertensive disorders of pregnancy lowered TREC. Hypertensive disorders of pregnancy lowered KREC and intrapartum fever >38 °C increased it. Low TREC and KREC values were not associated to the risk of developing early-onset sepsis and late-onset sepsis. Conclusion: TREC and KREC levels are lower in preterm than term infants, but this did not increase the risk of neonatal sepsis.